Food chemical safety : Volume 2 : Additives - David H. Watson (Cambridge, England : Woodhead Publishing Limited, 2000)
The regulation of additives in the EU.--The regulation of additives in the USA.--Analysis additives, Risk analysis food additives.--Analitycal mmethod: quality control and selection.--New method in detecting food additives.--Adverse reactions to food additives.--Specific additives: colorants.--Safety assessment of flavor ingredients.--Sweeteners.--Food additives, other than colours and sweeteners.--Case study: antioxidant preservatives.
Incluye References al final de cada capitulo, Index
Audiencia general
Keywords: Tecnología química; Aditivos para alimentos